2022
DOI: 10.25077/jikesi.v2i3.546
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Pemeriksaan CT Scan Abdomen pada Pasien Tumor Ovarium di RSUP DR. M. Djamil Padang Tahun 2019-2020

Abstract: Latar Belakang : Tumor ovarium merupakan tumor ganas terbanyak ke 3 pada wanita. Keterlambatan mendiagnosis dapat meningkatkan morbiditas dan mortalitas dari tumor ovarium. Computerized Tomography Scanner (CT-scan) abdomen merupakan pemeriksaan radiologi pertama untuk mendeteksi dan menentukan stadium keganasan ovarium. Penelitian ini bertujuan untuk mengetahui gambaran CT-scan abdomen pasien tumor ovarium. Objektif: Untuk mengetahui gambaran pemeriksaan CT-Scan Abdomen yang dilakukan pada pasien tumor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…It was shown that 2 subjects showed extreme differences with the linear measurement results which had greater measurement results compared to the active contour Laplacian of Gaussian (LoG), this occurred in subjects with cystic ovarian neoplasms which had a tendency to malignancy (malignant) characterized by edge surfaces patchy, containing one or more complex mixtures Vol.2, No.11, October 2023 such as solid masses, hemorrhagic components, and septations. This is in line with research conducted by Hafidz (2020) which revealed that malignant ovarian tumors have cystic, mixed, solid, and ascitic components (Aryan et al, 2020). So it is recommended to measure the volume of cystic ovarian neoplasms with a tendency to malignancy using the active contour Laplacian of Gaussian (LoG) volume measurement technique because it has higher sensitivity, utilizing the reliability of edge detection to measure each slice containing clinical information following the shape and size according to surface conditions and the shape.…”
Section: A Better Technique For Producing Volume Measurements Of Cyst...supporting
confidence: 92%
“…It was shown that 2 subjects showed extreme differences with the linear measurement results which had greater measurement results compared to the active contour Laplacian of Gaussian (LoG), this occurred in subjects with cystic ovarian neoplasms which had a tendency to malignancy (malignant) characterized by edge surfaces patchy, containing one or more complex mixtures Vol.2, No.11, October 2023 such as solid masses, hemorrhagic components, and septations. This is in line with research conducted by Hafidz (2020) which revealed that malignant ovarian tumors have cystic, mixed, solid, and ascitic components (Aryan et al, 2020). So it is recommended to measure the volume of cystic ovarian neoplasms with a tendency to malignancy using the active contour Laplacian of Gaussian (LoG) volume measurement technique because it has higher sensitivity, utilizing the reliability of edge detection to measure each slice containing clinical information following the shape and size according to surface conditions and the shape.…”
Section: A Better Technique For Producing Volume Measurements Of Cyst...supporting
confidence: 92%